2011
DOI: 10.3362/1756-3488.2011.040
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining school hand washing and water treatment programmes: Lessons learned and to be learned

Abstract: In Nyanza Province, Kenya, a sustainability evaluation of 55 pilot primary schools 2.5 years after the implementation of the Safe Water System (SWS) intervention revealed that programme activities were not successfully sustained in any of the schools visited. The most common criterion met was drinking water provision. We identified six enabling environment domains: financial capacity; accountability; technical feasibility and availability; community support; school leadership and management; and student engage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 7 publications
1
64
0
Order By: Relevance
“…These findings are supported by a previous study by [13] which found a statistical significance in message diffusion from schools to households as a result of the same programme. In this regard, we argue that there is more to learn from school WASH programme strategies of using children as health messages ambassadors to bridge the gap between knowledge and practice.…”
Section: Discussionsupporting
confidence: 82%
“…These findings are supported by a previous study by [13] which found a statistical significance in message diffusion from schools to households as a result of the same programme. In this regard, we argue that there is more to learn from school WASH programme strategies of using children as health messages ambassadors to bridge the gap between knowledge and practice.…”
Section: Discussionsupporting
confidence: 82%
“…Although all intervention schools were supplied soap, the majority of schools did not consistently provide soap for hand washing during all four follow-up observation visits. Potential reasons for lack of hand washing water and soap provision by school administrations may include water accessibility difficulties, prevailing social norms among teachers themselves, and lack of institutional incentives and accountability 11,21. Within the schools that provided hand washing water and soap, not all pupils observed using the latrine practiced HWWS.…”
Section: Discussionmentioning
confidence: 99%
“…A school sustainability assessment found 1 of 55 schools providing soap for hand washing 3 years after a hygiene intervention, with 61% of school officials citing cost as one of the barriers to soap provision. Inability to prevent the theft of bar soap and lack of prioritization of soap by school administrators were also cited as barriers 21. A hand rinse study measuring Escherichia coli contamination on pupils' hands in a subset of intervention schools—one arm receiving hygiene promotion and the other arm receiving hygiene promotion with the addition of newly constructed latrines—found that the risk of detecting E. coli on girl pupils' hands was 2.6 times higher in schools that had received sanitation improvements in addition to hygiene promotion compared with control schools that did not receive any intervention ( P < 0.01) 22.…”
Section: Study Background and Objectivesmentioning
confidence: 99%
“…Results revealed that only 2 per cent of the pilot schools provided soap for handwashing on the day of the assessment. The two main barriers to soap provision identifi ed during the sustainability assessment based on interviews with teachers were soap theft (29 per cent) and insuffi cient or lack of school funds (60 per cent) (Saboori et al, 2010).…”
Section: Background Of Interventionmentioning
confidence: 99%